The influence of dental prostheses on the production of fricatives - Horga, Damir; Badel, Tomislav; Vidović, Ana; Liker, Marko (2012)
The loss of teeth and the wearing of dentures or dental prostheses create changes in the anatomical features of the vocal tract. Changes in the vocal tract produce changes in speakers' habitual articulatory programmes in order to produce intelligible speech. The articulatory equivalence principle enables speakers to produce acoustically relatively acceptable speech. However, differences in speech production between patients with dental prostheses and healthy speakers can still be observed, especially in aerodynamically demanding sounds, such as fricatives. Differences in speech production within the group of prostheses-wearing patients can also be observed, often depending on the type of the prosthesis used. In the present investigation we analyse the production of fricatives in speakers with dental prostheses, depending on the type of the prosthesis (N=30) and compare their production with eugnathic controls matched in age (N=10). The speech of 30 dental-prostheses-wearing patients was also analysed with and without prosthesis in situ. The productions of six Croatian fricatives were analysed: /f/, /s/, /z/, /š/, /ž/ and /h/. The speech material consisted of 54 VCV meaningless sequences (V represented /i/, /a/, /u/, while C represented one of the six fricatives). Five acoustic variables were measured: 1. centre of gravity of the noise spectrum, 2. standard deviation of the centre of gravity, 3. skewness, 4. kurtosis and 5. fricative duration. The speech material was recorded in the standard phonetic laboratory conditions in a sound treated room. The acoustic analysis was performed by means of the Praat programme and MS Excel was used for statistical analyses. The results showed that the acoustic characteristics of the sounds produced with the prostheses were closer to the acoustic characteristics of the controls compared to the characteristics of sounds produced without prostheses.
Projekt MZOS
Projekt MZOS
ENG